METTL14-mediated m6A modification upregulates HOXB13 expression to activate NF-κB and exacerbate cervical cancer progression - Qian Li; Na Zhao; Xuejing Ding; Jufen Zhao (Molecular & Cellular Oncology)
Cervical cancer (CC) is one of the common malignant tumors in women, and the incidence rate is located in the second place of female tumors. As a major RNA N6-methyladenosine (m6A) methyltransferase, methyltransferase-like 14 (METTL14) is involved in tumor progression by catalyzing methylation modifications in mRNAs. However, the molecular mechanism of METTL14-mediated m6A modification in CC remains not fully revealed. The expression of METTL14 was detected by RT-qPCR and western blot. Cell function was assayed by cell counting kit-8 (CCK-8) assay and flow cytometry analysis. Methylated RNA immunoprecipitation (MeRIP) was used to confirm the relationship between METTL14 and homeobox B13 (HOXB13). In our study, we found that the level of METTL14 was elevated in CC tissues and cells compared with their controls. The inhibition of METTL14 significantly impaired cell proliferation and the epithelial-mesenchymal transition (EMT) process, while also induced apoptosis in HeLa and C33A cells. Furthermore, our findings indicated that homeobox B13 (HOXB13) was a target of METTL14, which positively regulated the expression of HOXB13 in an m6A-dependent manner. Rescue experiments indicated that overexpression of HOXB13 effectively reversed the tumor suppression induced by METTL14 knockdown. Finally, we confirmed that METTL14-modified HOXB13 exerted an oncogenic effect through activation of the nuclear factor kappa B (NF-κB) pathway. In conclusion, our data demonstrated that the m6A modification of HOXB13, mediated by METTL14, facilitated the advancement of CC through targeting the NF-κB pathway, which may be a potential molecular target for the treatment of CC.